2016
DOI: 10.1080/08927014.2015.1131822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface-active block copolymers with oxyethylene and fluoroalkyl side chains on the antifouling performance of silicone-based films

Abstract: Block copolymers made from a poly(dimethyl siloxane) (Si) and a poly(meth)acrylate carrying oxyethylene (EG) or fluoroalkyl (AF) side chains were synthesized and incorporated as surface-active components into a silicone matrix to produce cross-linked films with different surface hydrophilicity/phobicity. Near-edge X-ray absorption fine structure (NEXAFS) studies showed that film surfaces containing Si-EG were largely populated by the siloxane, with the oxyethylene chains present only to a minor extent. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 81 publications
(81 reference statements)
1
31
0
Order By: Relevance
“…Secondly, the surface‐active copolymer that more effectively limited the attachment or promoted the release of U. linza was the fluorine‐free amphiphilic copolymer, containing only the polysiloxane and PEG side chains. Similar results were obtained when the FR performance against U. linza of two different surface‐active copolymers composed of the same PDMS block and a different poly(meth)acrylate block carrying PEG or perfluorohexylethyl side chains were compared . The fluorine‐free amphiphilic block copolymers showed a higher removal of sporelings with respect to the fluorinated block copolymers.…”
Section: Amphiphilic Surface‐active Polymerssupporting
confidence: 72%
“…Secondly, the surface‐active copolymer that more effectively limited the attachment or promoted the release of U. linza was the fluorine‐free amphiphilic copolymer, containing only the polysiloxane and PEG side chains. Similar results were obtained when the FR performance against U. linza of two different surface‐active copolymers composed of the same PDMS block and a different poly(meth)acrylate block carrying PEG or perfluorohexylethyl side chains were compared . The fluorine‐free amphiphilic block copolymers showed a higher removal of sporelings with respect to the fluorinated block copolymers.…”
Section: Amphiphilic Surface‐active Polymerssupporting
confidence: 72%
“…Recent work utilized siloxane block copolymers with either a fluoroalkyl-containing or a PEG-containing block as additives to a PDMS network. 49 While this showed that fluoroalkyl and PEG chain groups acted independently, our goal was to ascertain whether combining these functionalities into one block copolymer could provide additional synergistic benefits of both groups in one film. It has been hypothesized that the combination of polar (PEG) and non-polar (fluoroalkyl/PDMS) units 4 creates an "ambiguous" surface, in which the fouling species encounters a surface that spontaneously alternates between polar and non-polar character.…”
Section: Introductionmentioning
confidence: 99%
“…However, the more marked hydrophobic nature of the FA co‐units of the latter leads to a lower T c than that reported for the corresponding homopolymer (∼66 °C) . The inclusion of low surface energy fluoroalkyl side chains in a polymer structure is, in fact, known to drastically enhance the hydrophobic and lipophobic nature of the entire system which results in a strong capability to self‐assemble in solution, in bulk and at the surface of thin films …”
Section: Resultsmentioning
confidence: 96%